2019
DOI: 10.1016/j.jtcvs.2018.08.107
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis coronary revascularization and postdialysis mortality

Abstract: Coronary artery bypass grafting (CABG) is associated with better survival than percutaneous coronary intervention (PCI) in patients with mild-to-moderate chronic kidney disease (CKD) and End-Stage Renal Disease (ESRD). However, the optimal strategy for coronary artery revascularization in advanced CKD patients who transition to ESRD is unclear. Methods: We examined a contemporary national cohort of 971 US veterans with incident ESRD, who underwent first CABG or PCI up to 5 years prior to dialysis initiation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Eleven studies involving 26,441 patients (PCI group: 13,217; CABG group: 13,224) were included in the final analysis, including five subanalyses of RCTs and six propensity-matched registries, [17][18][19][20][21][22][23][24][25][26][27] published between 2005 and 2019 ( Figure 1). The main characteristics of the eligible studies are presented in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies involving 26,441 patients (PCI group: 13,217; CABG group: 13,224) were included in the final analysis, including five subanalyses of RCTs and six propensity-matched registries, [17][18][19][20][21][22][23][24][25][26][27] published between 2005 and 2019 ( Figure 1). The main characteristics of the eligible studies are presented in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Of the 11 studies, two compared PCI using bare-metal stent (BMS) versus CABG, 17,25 five compared PCI using DES versus CABG, 20,21,23,24,26 and the remaining four compared PCI using mixtures of BMS and DES versus CABG. 18,19,22,27 Overall, nine studies included multivessel disease with no or very few left main disease, [17][18][19][20][21][22][23]25,27 one study enrolled both multivessel and left main disease, 26 and the remaining one study enrolled only left main disease. 24 The clinical characteristics of the patients appear in Table 2.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…1C). 14 Finally, the 5-year results of the EXCEL trial were presented. The trial compared CABG versus PCI in patients with left main CAD and a SYNTAX score less than 32.…”
Section: Cabg Versus Pcimentioning
confidence: 99%
“…Patients with CKD are also at risk for acute kidney injury (AKI), a common complication after CABG or PCI (5), and for progression to end-stage renal disease (6). Although many studies have concluded that PCI preserves renal function better (5,7), most of these studies have been conducted on a short-term follow-up, and data on other kidney-related outcomes such as initiation of dialysis or kidney transplant are scarce.…”
Section: Introductionmentioning
confidence: 99%